Decadal variability in coastal phytoplankton community composition in a changing West Antarctic Peninsula. (June 2017) - Schofield, Oscar; Saba, Grace; Coleman, Kaycee; Carvalho, Filipa; Couto, Nicole; Ducklow, Hugh; Finkel, Zoe; Irwin, Andrew; Kahl, Alex; Miles, Travis; Montes-Hugo, Martin; Stammerjohn, Sharon; et al.
Abstract: The coastal waters of the West Antarctic Peninsula (WAP) are associated with large phytoplankton blooms dominated by large (>20 µm) diatoms however, nanoplankton (<20 µm) are also an important component of the food web. The dominant nanoflagellates in the WAP are cryptomonad algae. Using a twenty-year time series collected by the Palmer Long Term Ecological Research program at the United States Palmer Research Station, we assessed long-term patterns and stability in the coastal phytoplankton communities in the WAP. There was significant interannual variability in the integrated water column chlorophyll a (chl- a ) concentrations, which varied by a factor of 5 over the 20-year time series. There has been a significant positive increase in the seasonally integrated concentration of chl- a over the time series. The dominant phytoplankton were diatoms, with cryptophytes the second most abundant. Mixed flagellates also constituted a significant fraction of the chl- a but showed less inter a nnual variability than diatoms and cryophytes. Peak phytoplankton biomass was observed in summer months, when monthly averaged wind speed was lower than in the fall and autumn. Cryptophytes were most abundant during the summer months (December-January) after the seasonal retreat of sea ice. While diatoms were observed over the full range of observed salinities 32–34.5) as well as over the full range of in situ temperatures (−1.5 to 2.5 °C), the cryptophyte populations were observed in locations with lower salinity 32.5–33.75) and colder water (−1 to 1 °C). Environmental factors that favored a shallower seasonal mixed layer resulted in larger diatom blooms compared to the other phytoplankton taxa. During summer with lower phytoplankton biomass, a larger proportion of the chlorophyll a was associated with cryptophytes. These results demonstrate that continued temperature changes along the West Antarctic Peninsula will result in changes in phytoplankton concentration and community composition, which has significant ramifications for the food web. Highlights: Sea ice distributions in Antarctic Peninsula affect phytoplankton biomass/composition. The dominant phytoplankton groups are diatoms and cryptophytes, at Palmer Station. Sea ice increases associated with phytoplankton concentrations at Palmer Station.